(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The forms of narration of the short story by Susan Elizabeth Hill «A Bit of Singing and Dancing» as the means of revealing the person’s imaginary liberation and the ways of the building-up the selfless human-being’s life-tragedy are analyzed in the article. By means of imaginary dialogues, attempts of self-assessment of the main character, the omniscient narrator discovers and underlines the true state of her mind and spirit.